Localizing global sport for development - Lindsey, Iain (Globalizing Sport Studies, 2017)
This jointly authored book extends understanding of the use of sport to address global development agendas by offering an important departure from prevailing theoretical and methodological approaches in the field. Drawing on nearly a decade of wide-ranging multidisciplinary research undertaken with young people and adults living and working in urban communities in Zambia, the book presents a localised account that locates sport for development in historical, political, economic and social context. A key feature of the book is its detailed examination of the lives, experiences and responses of young people involved in sport for development activities, drawn from their own accounts. The book's unique approach and content will be highly relevant to academic researchers and post-graduate students studying sport and development in across many different contexts.